Pengaruh Motivasi Kerja Budaya Organisasi dan Komunikasi Karyawan Terhadap Kinerja Karyawan (studi karyawan PT. Energi Lautan Nusantara Plant 1 Malang) - Ajiningtyas, Rahtanaya; Sunaryo, Hadi; Suharto, M. Khoirul Anwarudin Broto (UNIVERSITAS ISLAM MALANG, 2024)
AbstractÂ The study aims to determine the effect of Work Motivation, Organizational Culture and Employee Communication (Case study of employees of PT. Energi Lautan Nusantara Plant 1 Malang).Â This type of research uses a quantitative approach and the data collection method used in this research is a questionnaire. The sample in this study amounted to 41 respondents. The method of analysis used in this study is multiple linear analysis with hypothesis testing using the F test and t test. Based on the results of this study indicate that Work Motivation, Organizational Culture and Employee Communication simultaneously affect Employee Performance while partially Work Motivation has no effect on Employee Performance, Organizational Culture affects Employee Performance and Employee Communication affects Employee performance.Â Keywords : Work Motivation, Organizational Culture, Employee Communication, Employee Performance.